Varitions in physical characteristics of rice (Oryza sativa L.) grains - Teng, S.; Vergara, B.S; Alejar, Arcelia A. (Asia life sciences :the international journal of life sciences., 1993)
"Seventy-two conventional rice varieties and hybrids were studied to determine the relationship and variations of physical characteristics in grains. Results showed that the weight of grain, brown rice, endosperm and embryo were positively correlated with grain width and thickness among varieties. These characters were variable and differed even within a variety, with a high percentage of variance for embryo weight. Multiple regression analysis showed that in conventional varieties or cultivars, grain width contributed more to weight while in hybrid, it was grain thickness. Moreover, heavy grains in conventional varieties had big embryos. However, this correlation was not true in the hybrids tested. Significant differences in hull weight were obtained among varieties. The variability in all the physical traits measured indicated the possibility of improving grain quality in a single variety, particularly on the same individual spikelet. Production of heavy brown rice or increase in grain yield is possible through the development of thinner hulls and hence, the probability of increased milling returns."